Observational signatures of black hole accretion: rotating versus spherical flows with tilted magnetic fields. Issue 1 (10th June 2022) - Jia(贾 赫), He; White, Christopher J; Quataert, Eliot; Ressler, Sean M
ABSTRACT: We study the observational signatures of magnetically arrested black hole accretion with non-rotating inflow on to a rotating black hole; we consider a range of angles between the black hole spin and the initial magnetic field orientation. We compare the results of our general relativistic magneto-hydrodynamic simulations to more commonly used rotating initial conditions and to the Event Horizon Telescope (EHT) observations of M87. We find that the mm intensity images, polarization images, and synchrotron emission spectra are very similar among the different simulations when post-processed with the same electron temperature model; observational differences due to different electron temperature models are significantly larger than those due to the different realizations of magnetically arrested accretion. The orientation of the mm synchrotron polarization is particularly insensitive to the initial magnetic field orientation, the electron temperature model, and the rotation of the inflowing plasma. The largest difference among the simulations with different initial rotation and magnetic tilt is in the strength and stability of the jet; spherical inflow leads to kink-unstable jets. We discuss the implications of our results for current and future EHT observations and for theoretical models of event-horizon-scale black hole accretion.